Vesico‐ureteral reflux - PALACIOS, A. (2006)
Arch Esp Urol. 2006 Nov;59(9):924. [Vesico-ureteral reflux] [Article in Spanish] Palacios A, de Castro R, Reis A. Servicio de Urología, Hospital Pediátrico Maria Pía, Porto, Portugal. aphmmx5@hotmail.com PMID: 17190222 [PubMed - indexed for MEDLINE]